Answer :

Let Sn denotes the sum of first n terms of an AP.


Sum of first n terms = Sn = 5n - n2


Then nth term is given by: an = Sn - Sn - 1


an = (5n - n2) - [5(n - 1) - (n - 1)2]


= (5n - n2) - [5n - 5 - (n2 + 1 - 2n)]


= 5n - n2 - 5n + 5 + n2 + 1 - 2n


= 6 - 2n

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses